From brewery waste to agricultural wealth: Enhancing nitrogen use efficiency and productivity of maize through brewery sludge and blended NPS fertilizer in North Mecha District, Northwestern Ethiopia - Fenta Assefa; Yigrem Mengist; Habatamu Yigermal; Kelemu Nakachew (PLoS ONE, 2025)
The expansion of brewery factories with huge production potential of brewery sludge in Ethiopia presents a significant opportunity to enhance sustainable soil and crop productivity. Hence, this field experiment was conducted in North Mecha district, Northwestern Ethiopia, to improve the yield and nnitrogen use efficiency of maize by applying brewery sludge (BS), blended nitrogen, phosphorous and sulfur (NPS) fertilizers alone and in combination. Six treatments (T1: control, T2: 100% recommended dose of blended nitrogen, phosphorous, sulfur (RDNPS (100 kg NPS ha-1)); T3: 75% RDNPS +  25% recommended dose of brewery sludge (RDBS); T4: 50% RDNPS +  50% RDBS; T5: 25% RDNPS +  75% RDBS; T6: 100% RDBS (10 t BS ha-1) were laid out in a Randomized Complete Block Design (RCBD) with three replications. The results revealed that both single and combined fertilizer applications resulted in higher production, nitrogen uptake, and efficiency as compared to no fertilizer application. Notably, the combined application of 75% RDBS with 25% RDNPS produced the highest above-ground biomass yield (23161.9 kg ha-1), grain yield (10620.6 kg ha-1), stover yield (12541.3 kg ha-1), harvest index (45.85%), nitrogen concentration in grain (1.71%) and stover (1.00%), as well as grain (181.72 kg ha-1), stover (124.17 kg ha-1), and total (305.89 kg ha-1) nitrogen uptake. Furthermore, the combined application of 75% RDBS with 25% RDNPS produced the highest grain yield (10620.6 kg ha-1), net benefit (170987.97 Ethiopian Birr (ETB) ha-1), and an acceptable marginal rate of return (MRR) (12613.93%) for maize production in the region. Hence, the study reveals that using BS and blended NPS at precise ratios can improve maize productivity in the North Mecha district. However, as the experiment was carried out only in one location for one cropping season, further studies at different locations for several years or seasons should be conducted to come up with strong and reliable recommendations.